DOES FISCAL DECENTRALIZATION INCREASE THE CAPITAL SPENDING ON INFRASTRUCTURE? - Prasetyaningtyas, Yunika Nur (FIA UB, 2013)
Abstract: Does Fiscal Decentralization Increase the Capital Spending on Infrastructure? This study examines the relation between capital spending on infrastructure and fiscal decentralization in East Java, Indonesia. The need for this research based on the fact that most of capital spendingâ budget is spent for infrastructure, and local governmentâs executive, Bupati/Walikota, tends to abuse his power to win the next election. This investigation, based on the theory of political business cycle uses data from 38 kabupaten/kota in East Java Province to estimate how far is the impact. In finding out the relationship between capital spending and fiscal decentralization, I select five bakorwil as representative. They are Bakorwil Madiun, Bojonegoro, Malang, Pamekasan and Surabaya. Finding that there is relationship between capital spending and fiscal decentralization, in which kabupaten/kota will increase their capital spending duringÂ the local election. The pattern is the same, that in average of 6-year observation in the five bakorwil, most of kabupaten/kota spend their capital spending on roads, irrigation and installation, but the difference is in distribution. Keywords: capital spending, fiscal decentralization, political business cycle Abstract: Apakah Desentralisasi Fiskal Meningkatkan Belanja Modal Infrastruktur?. Penelitian ini menelaah lebih dalam hubungan belanja modal di sektor infrastruktur dan desentralisasi fiscal di Jawa Timur, Indonesia. Target dari penelitian ini berdasar pada data banyaknya belanja modal yang dialokasikan di sektor infrastruktur, selain itu Bupati cenderung untuk menyalahgunakan jabatannya untuk memenangkan pemilihan berikutnya. Investigasi ini berdasar pada teori âpolitical business cycleâ dengan data dari 38 Kabupaten/kota di Jawa Timur guna mengukur sejauh mana dampaknya. Untuk menemukan hubungan antara belanja modal dan desentralisasi fiskal, saya mengelompokkannya dalam lima bakorwil, yaitu Bakorwil Madiun, Bojonegoro, Malang, Pamekasan and Surabaya. Disimpulkan bahwa belanja modal di sektor infrastruktur meningkat signifikan menjelang/selama pilkada di lima bakorwil, namun distribusi besarnya berbeda dalam belanja modal jalan, irigasi dan instalasi. Kata kunci: belanja modal, desentralisasi fiskal, teori political business cycle